Preliminary Physical and Mathematical Model of the Recoil Operated Firearm within the Bolt Recoil Period - Damian SZUPIEŃKO (Wstępny model fizyczny i matematyczny działania broni z odrzutem lufy w okresie odrzutu zamka, 2021)
This paper presents a preliminary physical and mathematical model which describes the specific action of an automatic, short recoil operated firearm with an accelerator. The model includes the characteristic stages of the automatic action for a short recoil operated firearm (during one half of a single shot cycle), which enables simulation and assessment of the effect of the firearm’s system design parameters on the recoil velocities in specific recoil assembly components.
Keywords: Modelowanie działania broni automatycznej